Exploring teaching practice supervisors’ experiences of student support in an open, distance and e-learning institution - Sethusha, Mantsose Jane (Penerbit Universiti Kebangsaan Malaysia, 2020)
Teaching Practice is an integral component of Initial Teacher Education, and an accreditation requirement as outlined in the Minimum Requirements for Teacher Education Qualifications policy document in South Africa. Supervisors play an important role in providing professional support and assessing student teachers during their school placement periods. This study explored Teaching practice supervisors’ experiences, understanding and provision of student support in an Open, Distance and e-Learning environment. The theoretical framework that underpins this research is the Humanistic Counselling Model framework, which emphasizes a person-centred humanistic approach. This is relevant in the sense that the research focuses on supervisors own reflections of their work as unique individuals, how they experience their roles and how they deal with daily challenges. In-depth, semi-structured interviews allowed supervisors to share their practices, experiences and understanding of student support during Teaching Practice assessment visits. Data was analysed through content analysis. The findings revealed that supervisors’ support puts emphasis on lesson planning, lesson presentation, assessment as well as overall classroom management and organization. Evidence gleaned from the study also suggest implications for teaching practice supervisors in relation to support in an Open, Distance and e-Learning environment.